“After-birth abortion” aka infanticide: the controversy reemerges - Tham, L.C., Joseph (Studia Bioethica, 2013)
Recent medical ethics literature has proposed the acceptability of killing new-born infants, calling it “after-birth abortion” which is another euphemism of infanticide. This article looks at the history behind this thinking and analyzes the serious problems associated with this proposal.